Phytoconstituents and antimicrobial activity of Melaleuca leucadendron leaf essential oil from Venezuela - González de Colmenares, Nélida; Ojeda de Rodríguez, Graciela; Prieto, Avismelsi; Crescente, Oscar; Cabrera, Lilibeth (Ciencia, 1970)
The essential oil composition of Venezuelan Melaleuca leucadendron leaves was determined. The oil was extracted by hydrodistillation and analyzed by HRGC and GC-MS. Among the 44 constituents identified, 1.8-cineole (38.4%). nerolidol (28.7%), alloaromadendrene (14.4%) and a-terpineol (12.6%) were the most abundant. The 1,8- cineole content was an indication that this essential oil belongs to the chemotype I. The essentid oil was active against BaciIlus cereus and Staphylmaccus aureus, but was inactive against Escherichia coIi and Pseudomonas aeruginosa It also showed toxicity in the brine shrimp (Artemia salina) lethality test (LC50 (24 h) = 22. 25 Âµ/ml).